Impactos da deriva de herbicidas mimetizadores de auxina no crescimento e fisiologia de mudas de nogueira-pecã e oliveira - Rubert, Jaine (2021)
The State of Rio Grande do Sul (RS) is considered the third largest fruit producer in Brazil. Currently, fruit species such as pecan and olive have advanced in the productive market. This increase is the result of the valorization of the consumption of fruits obtained from these plants, as well as their adaptation to the southern Brazilian climate. However, the proximity of orchards with grain production areas makes the fruit species susceptible to damage from herbicide drift. Furthermore, the objective of this study was to evaluate the damage caused by 2,4-D and dicamba drift on the growth and physiology of pecan and olive trees. Accordingly, experiments were conducted in a greenhouse in a completely randomized design with four replications. The treatments were arranged in a factorial scheme where factor A consisted of auxin mimic herbicides and factor B consisted of eight doses: 0; 1.56; 3.125; 6.25; 12.0; 25.0; 50.0; and 100% of the recommended doses for desiccation of 2,4-D (670 g ae ha-1) and dicamba (720 g ae ha-1) herbicides. The applications were carried out on seedlings with a CO2 pressurized backpack sprayer with a spray volume of 150 L ha-1. The evaluations were executed at 24, 48, and 72 hours for the parameters of chlorophyll a fluorescence and gas exchange (also evaluated 30 days after application). Moreover, the height and diameter of the stem were measured, as well as notes for the plant phytotoxicity caused by the herbicides. Based on the results obtained, it was concluded that the herbicides caused damage to both morphological and physiological variables of the seedlings, reducing their growth.